The Effect of Financial Satisfaction to Financial Technology with Financial Planning as Mediation - Rachma Agustina; Meta Ardiana; Dwi Ari Pertiwi; Deasy Ervina (Jurnal Economic Resource, 2023)
This study aims to analyze and obtain empirical evidence on the effect of financial satisfaction on financial technology and financial planning as mediation variables.  The approach used is a quantitative approach with the help of the Smart PLS 4 tool. The data in this study used primary data with questionnaire techniques on PKK mothers in Talun Kidul Village, Sumobito District, Jombang Regency. The sample calculation uses a saturated sample of 40 respondents who were present at the time of sampling. This study uses outer model and inner model evaluation techniques with hypothesis testing using path analysis. The results showed that financial satisfaction affects financial technology; financial satisfaction affects financial planning; and financial planning affects financial technology. Financial planning variables as mediation show that financial planning variables can mediate financial satisfaction with financial technology.